The Dilemma Between Islamic Law And Local Tradition: A Critical Analysis of Consanguineous Marriage Practices (Rampanan Kapa’) In The Tana Toraja Community (Program Studi Hukum Keluarga Islam, 2025)
This study explores the complex relationship between Islamic law and local tradition through a critical analysis of consanguineous marriage practices, specifically Rampanan Kapa’ Sule Langngan Banua, in the Tana Toraja community. While this tradition is deeply embedded in the region's cultural identity and serves to preserve kinship ties and inheritance structures, it raises significant concerns within the framework of Islamic legal norms, particularly those related to mahram relationships. Using a qualitative case study approach, the research collected data through in-depth interviews with Muslim community members, traditional leaders, and religious scholars in Tana Toraja. The findings reveal a deep-rooted tension between cultural continuity and religious compliance, as some community members advocate for the tradition’s preservation, while others call for its reformation in line with Islamic principles. The study argues that the practice, although normative within customary law, contravenes the prohibitions outlined in Islamic jurisprudence and the Compilation of Islamic Law (KHI). Rather than acting as religious authorities (mufti or mufassir), this research adopts a socio-legal lens to assess the implications of consanguineous marriage in a multicultural and multi-religious setting. The study contributes to the discourse on legal pluralism and offers specific recommendations, including the integration of customary marriage education into local religious counseling programs, legal awareness campaigns for community leaders, and the formulation of local regulations (Perda) that respect cultural values while upholding Islamic legal principles.